Fracture location transition in constant load tests of a NiCrMoV steel welded joint - Shuo Weng; Yuhui Huang; Fuzhen Xuan; Songlin Zheng (Materials & Design, 2019)
The fracture location transition of the NiCrMoV steel welded joints induced by different tensile loads has been investigated through the constant load tests in 3.5 wt% NaCl at 180 °C. The mechanical properties of different zones in the welded joints were measured by the hardness measurement and localized tensile tests in air at room temperature. The corrosion properties were characterized by potentiodynamic polarization curve tests and scanning vibrating electrode technique (SVET) tests. The results reveal that the most susceptive corrosion zone and the weakest strength zone do not locate in same zone of the welded joint. This mismatch leads to the rupture locations of the welded joints change with the applied load in the constant load tests. For the applied load larger than or equal to 765 MPa, the rupture section locates in the middle of WM due to its weakest strength. But the fracture position shifts to the fusion zone for the applied load less than or equal to 760 MPa, which is attributed to stress corrosion cracking (SCC) originating from the pits under the combined effect of galvanic and stress-assisted corrosion. Keywords: Welded joint, Constant load test, Fracture location transition